2007
DOI: 10.2337/db06-0430
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the Amyloid-Degrading Enzyme Neprilysin in Mouse Islets and Potential Role in Islet Amyloidogenesis

Abstract: Islet amyloid contributes to loss of ␤-cell mass and function in type 2 diabetes. It is poorly understood how the building block of amyloid, islet amyloid polypeptide (IAPP), misfolds and accumulates within the islet to contribute to cellular dysfunction. We sought to determine whether neprilysin, an amyloid-degrading enzyme, is present in islets and plays a role in the accumulation of amyloid fibrils. Human IAPP (hIAPP) transgenic mice, a model of islet amyloid in which primarily male mice develop amyloid by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…At this time, the specific localization of neprilysin within the islet has not been clearly defined. Previously, using an immunohistochemical approach, we showed that islet neprilysin localized to both ␤-cells and non-␤-cells and is largely membranous with some cytoplasmic localization (8). Reports describing neprilysin in non-islet tissues also document that it is predominantly plasma membrane-bound; however, there is evidence in neurons that neprilysin is also localized in secretory vesicles (41).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…At this time, the specific localization of neprilysin within the islet has not been clearly defined. Previously, using an immunohistochemical approach, we showed that islet neprilysin localized to both ␤-cells and non-␤-cells and is largely membranous with some cytoplasmic localization (8). Reports describing neprilysin in non-islet tissues also document that it is predominantly plasma membrane-bound; however, there is evidence in neurons that neprilysin is also localized in secretory vesicles (41).…”
Section: Discussionmentioning
confidence: 98%
“…Neprilysin Enzymatic Activity Assay-Islet neprilysin enzyme activity was determined fluorometrically as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations